Challenges and pathways for parrotfish conservation in developing countries: lessons from the endemic and endangered greenbeak parrotfish Scarus trispinosus - Roos, Natalia C. (Frontiers in Ecology and Evolution, 2025)
The greenbeak parrotfish, Scarus trispinosus, is the largest southwestern Atlantic parrotfish, endemic to Brazil and targeted by reef-associated fisheries along the coast. After a sharp population decline, S. trispinosus is now considered one of the most endangered parrotfish worldwide. The lack of basic biological information has hindered the development of appropriate management policies, until recently. I compiled data on abundance, biomass, size class distribution, ecology, demography, and fisheries of S. trispinosus along the Brazilian coast to explore how Marine Protected Areas (MPAs) and newly implemented management strategies could support the species’ recovery and protection. I found that the Brazilian equatorial margin is nearly as important as the Abrolhos Bank in terms of S. trispinosus abundance. Shallower inshore reefs serve as nurseries, while larger individuals often occupy deeper offshore reefs. The estimated size and age of first maturity (39.2 cm in total length; 4.2 years) indicate that S. trispinosus is relatively long-lived and reaches sexual maturity later than other parrotfishes in the Caribbean and Pacific, highlighting its vulnerability. Most small-scale fishing targets immature individuals in inshore reefs, while recreational spearfishing primarily targets significantly larger individuals. While fishing is significant, the value chain of S. trispinosus is poorly understood, hindering the development of new tools to regulate its fishing. Brazilian MPAs protect some critical areas, but the species’ ongoing decline suggests that MPAs alone are insufficient without proper fisheries management. Although the most effective management strategy would likely be a fishing moratorium, as adopted in Belize, social challenges and the lack of political context in Brazil hinder its implementation. Alternatively, the Brazilian government has released the National Recovery Plan for Endangered Species, which restricts S. trispinosus fishing to multiple-use MPAs with proper regulatory measures, while prohibiting fishing for this species elsewhere on the coast. The development and adaptation of this novel strategy were made possible by advances in research over the past 10 years. However, some key areas still lack implementation, and it may be too early to determine whether the plan is effectively working. If effectively implemented and successful, it could serve as a model for managing parrotfishes elsewhere.